MORFOLOGICAL STATE OF RETINA IN RATS DURING SUBCUTANEOUS TRANSPLANTATION OF СRYOPRESERVED PLACENTA IN EXPERIMENTALLY INDUCED ACUTE ASEPTIC RETINITIS - Stetsuk, O.A.; Shepitko, K.V. (World of Medicine and Biology, 2019)
The study was carried out on 65 male rats of Wistar line, 55 of them being modeled aseptic retinitis by administering 5 mg of λ-carrageenan in 1 ml of NaCl solution. A single subcutaneous transplantation of cryopreserved placenta was performed. The control group included 10 rats. Morphological changes of the eye retina were studied at the early terms of the experiment. It was established that modeled aseptic retinitis has clear stages of inflamation (altiration, exudation and prolifiration). Changes were arising gradually starting from ganglion cell layer.
Keywords: cryopreserved placenta; λ-carrageenan; retina; aseptic retinitis